A review of under-frequency load shedding scheme on TNB system - Mohd. Zin, Abdullah Asuhaimi; Habibudin, Mohd. Hafiz; Aziz, M. S. (IEEE, 2004)
Safe operation of a power system will require that system frequency is kept within a specified range. When the generation is insuficient due to disturbances, the frequency might fall under the minimum allowable value which may lead to system blackout if not property counteracted. This frequency decline may be corrected by shedding certain amount OC load so that the system is back into balanced state. This paper reports a case study on Malaysia's TNB system. UFLS scheme used by TNB was reviewed, Then modification and improvement was made to reflect the current changes in the system making the scheme more .up to date. Et'fect of having more stages to reduce over shedding and combination of different amount of load at each stage are discussed.